Answer:
Option A.
Explanation:
We will write all the justifications for each step
Step 1 to step 2.
3x + 9 - 7x = x + 10 + x
-4x + 9 = 2x + 10
combining like terms on each side of the equation.
Step 2 to step 3.
-4x + 9 = 2x + 10
-6x + 9 = 10
Here [-4x - 2x + 9 = 2x - 2x + 10]
So, the subtraction property of equality is the justification.
Step 3 to step 4.
-6x + 9 = 10
-6x = 1
Here [ -6x + 9 - 9 = 10 - 9]
So subtraction property of the equality is followed.
Step 4 to step 5.
x = -
![(1)/(6)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1hfsyqujpiw8kz1nwo0zeow75fj0n2oyv6.png)
here [
]
Division property of equality
Therefore, Option A. is true for the step 2 to step 3.